Novel Approach to the Detection of Left Ventricular Hypertrophy Using Body Mass Index–Corrected Electrocardiographic Voltage Criteria in a Group of African Ancestry. Issue 9 (9th June 2016) - Robinson, Chanel; Woodiwiss, Angela J.; Libhaber, Carlos D.; Norton, Gavin R.
Abstract: Background: Electrocardiographic (ECG) QRS voltages used to generate criteria for left ventricular hypertrophy (LVH) detection are considerably attenuated by obesity. This effect renders the utility of ECG criteria to detect LVH in obese individuals of African ancestry to be of limited value. Hypothesis: A novel approach to correcting QRS voltages for the attenuating effect of body mass index (BMI) will improve the ability of ECG criteria to detect LVH in a group of African descent. Methods: Left ventricular mass was determined from echocardiography in 661 randomly selected participants (43.0% obese) of black African ancestry in South Africa. Results: As compared with Cornell and Sokolow‐Lyon voltage criteria, BMI best correlated with RaVL, Gubner‐Ungerleider, and Lewis QRS complex voltages, but these relations were noted only in those with BMI <29 kg/m 2 . Correcting RaVL and Lewis voltages by the difference in the slope of BMI‐voltage relations in those with BMI <29 kg/m 2 vs those with BMI ≥29 kg/m 2 showed the greatest performance for LVH detection (uncorrected RaVL : 0.695 ± 0.025, corrected RaVL : 0.733 ± 0.022; P < 0.0001), and also increased the sensitivity (uncorrected RaVL : 30.6%, corrected RaVL : 42.4%; P < 0.0005) with no significant change in specificity (uncorrected RaVL : 86.3%, corrected RaVL : 83.0%; P = 0.28). Conclusions: We offer a novel approach to correcting ECG voltages for the attenuating effects of obesity in individuals of African ancestry, and this improves the performance and sensitivity for LVH detection.